Cold atmospheric plasma, a new strategy to induce senescence in melanoma cells - Arndt, Stephanie; Wacker, Eva; Li, Yang-Fang; Shimizu, Tetsuji; Thomas, Hubertus M.; Morfill, Gregor E.; Karrer, Sigrid; Zimmermann, Julia L.; Bosserhoff, Anja Katrin (Experimental Dermatology, 2013)
Over the past few years, the application of cold atmospheric plasma (CAP) in medicine has developed into an innovative field of research of rapidly growing importance. One promising new medical application of CAP is cancer treatment. Different studies revealed that CAP may potentially affect the cell cycle and cause cell apoptosis or necrosis in tumor cells dependent on the CAP device and doses. In this study, we used a novel hand-held and battery-operated CAP device utilizing the Surface Micro Discharge (SMD) technology for plasma production in air and consequently analysed dose-dependent CAP treatment effects on melanoma cells. After 2 min of CAP treatment, we observed irreversible cell inactivation. Phospho-H2AX immunofluorescence staining and Flow cytometric analysis demonstrated that 2 min of CAP treatment induces DNA damage, promotes induction of Sub-G1 phase and strongly increases apoptosis. Further, protein array technology revealed induction of pro-apoptotic events like p53 and Rad17 phosphorylation of Cytochrome c release and activation of Caspase-3. Interestingly, using lower CAP doses with 1 min of treatment, almost no apoptosis was observed but long-term inhibition of proliferation. H3K9 immunofluorescence, SA-ß-Gal staining and p21 expression revealed that especially these low CAP doses induce senescence in melanoma cells. In summary, we observed differences in induction of apoptosis or senescence of tumor cells in respond to different CAP doses using a new CAP device. The mechanism of senescence with regard to plasma therapy was so far not described previously and is of great importance for therapeutic application of CAP. © 2013 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Apoptosis; Melanoma cells; Plasma; Senescence